Investigation of the laminar separation-induced transition on two low-pressure turbine rotor blades. (1st January 2013) - Babajee, Jayson; Arts, Tony
The present study focuses on the assessment and the validation of the Langtry-Menter correlation-based transition model, recently implemented in the RANS code elsA from ONERA. The test cases are two low-pressure turbine (LPT) rotor blades, with different compressible Zweifel loading coefficients and different diffusion rates. The experimental outlet isentropic Reynolds number, based on blade chord and outlet isentropic velocity, ranges from 22, 000 to 250, 000 in order to investigate the complex separation-induced transition phenomenon. The turbulence intensity is the natural freestream turbulence of the facility (approximately 0.9%). The numerical test campaign provides good predictions for the low Zweifel loading coefficient case, even at really low outlet isentropic Reynolds number (22, 000). However, for the high Zweifel loading coefficient case, the calculations are not able to predict the flow behaviour. The authors stress the importance of the turbulence Reynolds number effect on the prediction of separationinduced transition for strong diffusion LPT blades associated to high Zweifel loading coefficient.